2017
DOI: 10.1108/mip-12-2015-0230
|View full text |Cite
|
Sign up to set email alerts
|

The importance of aesthetics on customers’ intentions to purchase smartphones

Abstract: Purpose The purpose of this paper is to examine how potential purchasers of a personal information, communication and entertainment device such as a smartphone, perceive the aesthetics of such a product. It then examines whether appreciation of the product’s aesthetics influences their purchase intention through different dimensions of perceived value drawn from perceptions of the product’s aesthetics, or whether there is a direct relationship from aesthetics to purchase intention. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 92 publications
3
57
1
26
Order By: Relevance
“…Later, Swilley (2012) treated overall appearance as an independent construct for testing and developed a measurement method for six constructs [37]. Toufani, Stanton, and Chikweche (2017) used Swilley's (2012) six constructs of aesthetics in their study of the aesthetics of smartphones [14]. The product form aesthetics in this study used four constructs of aesthetics from Swilley (2012) and Toufani, Stanton, and Chikweche (2017) [14,37], namely, color, texture/touch, shape, and overall appearance.…”
Section: Product Form Aestheticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Later, Swilley (2012) treated overall appearance as an independent construct for testing and developed a measurement method for six constructs [37]. Toufani, Stanton, and Chikweche (2017) used Swilley's (2012) six constructs of aesthetics in their study of the aesthetics of smartphones [14]. The product form aesthetics in this study used four constructs of aesthetics from Swilley (2012) and Toufani, Stanton, and Chikweche (2017) [14,37], namely, color, texture/touch, shape, and overall appearance.…”
Section: Product Form Aestheticsmentioning
confidence: 99%
“…Toufani, Stanton, and Chikweche (2017) used Swilley's (2012) six constructs of aesthetics in their study of the aesthetics of smartphones [14]. The product form aesthetics in this study used four constructs of aesthetics from Swilley (2012) and Toufani, Stanton, and Chikweche (2017) [14,37], namely, color, texture/touch, shape, and overall appearance. In addition, according to a recent study by Dehghani and Kim (2019) on smartwatches [38], this study added two constructs to the conceptual model, namely, screens size and uniqueness.…”
Section: Product Form Aestheticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the factors, visual aesthetics is proved to be critical in product design evaluation [3,4] by physiological analysis approaches [5] and user experience study [6]. The existing studies indicated that visual aesthetics is significantly influencing user preference [7] and stimulating users' purchase behavior [8][9][10], which has a crucial effect on promoting product acceptance [11]. Consequently, quantifying the visual aesthetics of design works by computational means is promising for various industries.…”
Section: Introductionmentioning
confidence: 99%